RETRACTED: Impact of salinity levels on the physical properties of irrigated meadow alluvial soils in Bukhara region - Umarov Otabek; Bafayeva Zahro; Qodirov Elbek (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001